Modelling of mechanical properties of eco-friendly composites derived from sugar palm tree - Sahari, J.; Maleque, Md. Abdul (AENSI Publications, 2015)
Eco-friendly composites have been successfully prepared from the source of sugar palm tree. The effect of fibre contents on mechanical properties of sugar palm fibre reinforced plasticized sugar palm starch (SPF/SPS) biocomposites have been performed and the experimentally tensile properties (tensile strength and young’s modulus) of biocomposites have been compared with the theoretical model of measurement. The biocomposites were prepared with different amounts of fibres (i.e. 10%, 20% and 30% by weight percent). The mechanical properties of plasticized SPS was found improved with the incorporation of SPF. Both approaches (experimental and theoretical) showed that the young’s modulus of the biocomposite is consistently increased when the sugar palm fibre (SPF) are placed into the sugar palm starch matrix (SPS). Surface morphological study through scanning electron microscopy showed homogeneous distribution of fibres and matrix with good adhesion which play an important role in improving the mechanical properties of biocomposites. The observed deviations between the experimental and theoretical values are explained by the simplifying model assumptions applied for the configuration of the composites, in particular the sugar palm starch composites.